2019
DOI: 10.1186/s12888-019-2205-5
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dysfunction in Chinese rural patients with schizophrenia

Abstract: Background Sexual dysfunction is common in patients with schizophrenia, however it is poorly studied in China, especially in primary health care institutions in rural areas. We investigated the prevalence of sexual dysfunction and its correlates including quality of life (QoL), in schizophrenia patients treated in primary care in a rural area in China. Method By using a random numbers table, 21 small town primary care service centers (from 63 totally) were selected in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 55 publications
3
12
1
Order By: Relevance
“…A difference between the sexes in the prevalence of sexual dysfunction among patients with schizophrenia is inconsistent in previous studies; some authors have reported higher rates of sexual dysfunction in female patients (Bianco et al, 2019;Huang et al, 2019), others have reported the opposite (Cutler, 2003), whereas some have discovered similar rates for both sexes (Fujii et al, 2010). Our study found that female sex was associated with sexual dysfunction in olanzapinetreated patients with schizophrenia.…”
Section: Discussioncontrasting
confidence: 82%
“…A difference between the sexes in the prevalence of sexual dysfunction among patients with schizophrenia is inconsistent in previous studies; some authors have reported higher rates of sexual dysfunction in female patients (Bianco et al, 2019;Huang et al, 2019), others have reported the opposite (Cutler, 2003), whereas some have discovered similar rates for both sexes (Fujii et al, 2010). Our study found that female sex was associated with sexual dysfunction in olanzapinetreated patients with schizophrenia.…”
Section: Discussioncontrasting
confidence: 82%
“…Other studies have suggested prevalence of dysfunction between 30 and 60% in drug-free patients with psychosis and prevalence as high as 80% in a more general population of men with schizophrenia (Ravichandran 2019). In a rural Chinese population with schizophrenia 71.3% reported sexual dysfunction and this was associated again with old age and with burden of negative symptoms (Huang 2019). Although there is a paucity of research into this area it has also been suggested that loss of interest in sex in people with schizophrenia is associated with advancing age, female gender, cardiovascular medication, negative symptoms and lower sexual self-efficacy (self-confidence and self-control in sexual experiences) (Bianco 2019).…”
Section: Mental Illness and Sexual Dysfunctionmentioning
confidence: 99%
“…Sexual dysfunction is a serious side effect that commonly manifests in patients with chronic schizophrenia (1)(2)(3). Previous studies have shown that the prevalence of global sexual dysfunction in schizophrenia patients ranged from approximately 16% to 96% (4)(5)(6). Generally, the illness itself and antipsychotic drugs both can lead to sexual dysfunction in schizophrenia patients (3,5,7).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the illness itself and antipsychotic drugs both can lead to sexual dysfunction in schizophrenia patients (3,5,7). Moreover, sexual dysfunction has a negative impact on treatment adherence and intimate relationships, especially in males (3,6,8,9). In addition, due to decreased libido and erectile dysfunction, most males with chronic schizophrenia are accompanied by low self-esteem (10,11) and depression (3,12), which reduce their motivation to seek intimacy and damage their marital relationships (13).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation